2008
DOI: 10.1111/j.1540-6237.2008.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Gerrymandering on Georgia's Mind: The Effects of Redistricting on Vote Choice in the 2006 Midterm Election*

Abstract: Objective. We make use of individual-level survey data from the 2006 midterm election in order to determine the degree to which redistricting affected the vote choice of whites residing in Georgia Congressional Districts 8 and 12. Methods. A multivariate probit model was used to assess the probability of voting for the GOP House candidate among voters represented by the same incumbent before and after redistricting versus voters who had been newly drawn into one of these districts. Results. Despite a national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…There is no stronger evidence for this than the fact that Marshall's core constituency is found in the city of Macon in District 8's most populous county (Bibb County). They were almost right and this is all the more remarkable considering that these redrawn whites were more likely to vote Republican (Hood and McKee 2008) in a short-term national climate that greatly favored the Democratic Party. Nonetheless, by saddling Marshall with a very high percentage of new, largely white constituents, Georgia Republicans expected to be able to defeat the incumbent.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…There is no stronger evidence for this than the fact that Marshall's core constituency is found in the city of Macon in District 8's most populous county (Bibb County). They were almost right and this is all the more remarkable considering that these redrawn whites were more likely to vote Republican (Hood and McKee 2008) in a short-term national climate that greatly favored the Democratic Party. Nonetheless, by saddling Marshall with a very high percentage of new, largely white constituents, Georgia Republicans expected to be able to defeat the incumbent.…”
Section: Resultsmentioning
confidence: 95%
“…Although the overall African American population slightly increased, this was offset by removing moderate-to-liberal metropolitan whites and replacing them with many more conservative rural whites (for details see Hood and McKee 2008). In the case of District 12, which neighbors District 8 to the east, the Democratic incumbent John Barrow lost his liberal stronghold of Athens-Clarke Countyhome to the University of Georgia.…”
mentioning
confidence: 99%
“…But other scholars remain much more skeptical about the effect of districting on competition (e.g., Glazer et al 1987, Ferejohn 1977, Masket et al 2012, Abramowitz 2006). Moreover, a few studies distinguish between partisan and bipartisan maps, and argue that partisan gerrymanders actually increase competition under certain circumstances (Gopoian and West 1984, Gelman and King 1994, Yoshinaka and Murphy 2011, Murphy and Yoshinaka 2009, Hood and McKee 2008. Recent scholarship has also focused on nonpartisan reforms, with independent commissions found to increase competitiveness (Carson andCrespin 2004, Lindgren andSouthwell 2013).…”
Section: B Competitivenessmentioning
confidence: 95%
“…As previous research has demonstrated (Hood and McKee 2008;), redistricting jeopardized the reelection bids of Congressmen Marshall (GA-8) and Barrow (GA-12) because redrawn constituents were much more likely to vote for the Republican challengers, two former Georgia U.S. House members (Mac Collins in By contrast, at the national level, the partisan difference shows that in 2006 Democrats outnumbered Republicans by 2 points (39%-37%). Under conditions of conflicting partisan tides such as these, with an unusually robust shift toward the national Democratic Party in the 2006 midterm countered by a persistent Republican realignment in Georgia, we hypothesize that both Democratic and Republican House members will receive a lower percentage of the vote from their redrawn constituents.…”
Section: Redistricting For the 2006 Midtermmentioning
confidence: 97%